Selenium nanoparticles enhance metabolic and nutritional profile in Phaseolus vulgaris: comparative metabolomic and pathway analysis with selenium selenate - Asmaa Abdelsalam; Fatma Abd El Lateef Gharib; Arezue Boroujerdi; Nada Abouelhamd; Eman Zakaria Ahmed (BMC Plant Biology)
Abstract Selenium is a beneficial element in agriculture, particularly for its potential to improve plant growth and stress tolerance at suitable concentrations. In this study, Phaseolus vulgaris was foliar-sprayed with selenium selenate (Se) or selenium nanoparticles (SeNP) at different concentrations during the vegetative stage; afterward, the seed yield was analyzed for metabolomics using 1H, J-resolved and HSQC NMR data, and NMR databases. A total of 47 metabolites were identified with sugars being the major chemical class. In the control sample, the most abundant sugar was stachyose (14.6 ± 0.8 mM). Among the identified alkaloids, the concentration of trigonelline was the highest (0.6 ± 0.08 mM). Chemometric and cluster analyses distinctly differentiated the control from the Se and SeNP-treated samples. Treatments with SeNP resulted in elevated concentrations of sugars, carboxylic acids, and sulfur-containing amino acids compared to control and Se treated samples. Conversely, betaine levels were higher in Se samples. The presence of Se and SeNP significantly decreased the levels of several aliphatic amino acids, e.g. alanine. The addition of 50 µM SeNP upregulated the levels of trigonelline and syringate by 2-fold and 1.75-fold, respectively, relative to the control. Pathway analysis indicated the most significantly altered pathways due to SeNP addition were arginine biosynthesis and nitrogen metabolism. The pathways influenced by Se addition were glyoxylate and dicarboxylate metabolism as well as glycine-serine and threonine metabolism. This study proved that SeNP are more efficient than Se in enhancing the metabolic profile of Phaseolus vulgaris which will have implications for agricultural practices, focusing on the sustainability and nutritional enhancement of crops.